Study of structural and electrical behavior of silicon-carbon nanocomposites via in situ transmission electron microscopy. (August 2022) - Yaakob, Yazid; Lin, Wei Ming; Rosmi, Mohamad Saufi; Yusop, Mohd Zamri Mohd; Sharma, Subash; Chan, Kar Fei; Asaka, Toru; Tanemura, Masaki
Abstract: In this work, we have studied the structural and electrical behavior of Si-incorporated carbon nanostructures (Si-CNS) by performing current-voltage (I-V) measurements using in situ transmission electron microscopy (TEM). The I-V measurement and TEM observation of the corresponding Si-CNS structural transformation during the process were investigated in detail. Structural transformation of Si-CNS was occurred at high electric current flow (~µA), and reached its peak before electrical breakdown damaging the nanostructures. The formation of few graphene layer from initially amorphous structure were observed with embedded Si particles. The graphitic structures significantly improve the Si-CNS electrical properties depending on the nanostructure shape and Si-C composition. The current increased up to ~24.8 μA for nanofiber, and ~3 mA for nanocone, indicating the improvement of Si-C matrix crystallinity and decrement of Si composition from sublimation due to current-induced Joule heating. In situ heating technique revealed that Si particle begin to agglomerate at ~500 °C and the graphitization on the Si surface occurred at > 700 °C in a low pressure environment (~10 −5 Pa). The combination of the in situ TEM study can be promising for further understanding of Si-C structural and electrical behavior towards the future development of next-generation electronic and energy applications. Graphical Abstract: ga1 Highlights: Nanostructure evolution of Si-C nanostructures during applied current flow. Effect of Si-C nanostructure and composition to electrical properties and current-induced Joule heating is discussed. Failure of Si-CNS from current breakdown is elucidated. Graphitization, diffusion path transition and sublimation of Si was substantiated through nanoscale structural analysis.